Estimating Return to Education Under Vertical Mismatch in the Job Market - Elamin, Obbey (The Arab Journal of Administration, 2023)
Education vertical mismatch occurs when an employee in the labour market works in a job that requires different schooling years than what s/he has acquired. This research analyses the impact of vertical mismatch on wage using cross-sectional data in three countries, Jordan, Tunisia and Egypt. The generalized method of moment is used to estimate the return of education under vertical mismatch in the job market. The results show that the return to education is close in the three countries and approximately 7% to 9% for each additional schooling year. On the other hand, the return of overeducation and undereducation is insignificant. Individuals receive the wages that are determined for their job positions, which creates a wage penalty that approximates 8% for each additional year of overeducation. The research suggests that it is important to focus on active labour market programmes to reduce the stock of mismatched workers, re-regulate the job-market to reduce the wage gap. Focus on institutional linkage between the education and business sectors to develop curriculums that in line with job-market requirements.